2007
DOI: 10.1007/s00125-007-0770-5
|View full text |Cite
|
Sign up to set email alerts
|

Human Krüppel-like factor 11 inhibits human proinsulin promoter activity in pancreatic beta cells

Abstract: The last paragraph of the Abstract should have read:Conclusions/interpretation In rodent beta cell lines, we demonstrate hKLF11 overexpression-mediated inhibition of human proinsulin gene expression and characterise a prominent role for the CACCC box in maintaining basal proinsulin promoter activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
2

Year Published

2009
2009
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 0 publications
4
7
2
Order By: Relevance
“…Our own research, however, could not confirm these findings. We observed that hKLF11 inhibits hInsP in rat INS-1E as well as mouse b-TC3 b-cells (Niu et al, 2007). A negative regulation of hInsP by cotransfected hKLF11 was also observed by others in mouse MIN6-m9 b-cells (Kuroda et al, 2009).…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…Our own research, however, could not confirm these findings. We observed that hKLF11 inhibits hInsP in rat INS-1E as well as mouse b-TC3 b-cells (Niu et al, 2007). A negative regulation of hInsP by cotransfected hKLF11 was also observed by others in mouse MIN6-m9 b-cells (Kuroda et al, 2009).…”
Section: Introductionsupporting
confidence: 78%
“…Construction of human KLF11 expression plasmid (hKLF11-pcDNA 3.1) and human insulin promoter-driven secreted alkaline phosphatase (SEAP) reporter plasmids (5 0 -deletion series À881 + 54 to À101 + 54hInsP-pSEAP) has been described previously (Niu et al, 2007). The human p300 coding sequence was subcloned from CMVß-p300 (kindly provided by Timothy J. Kieffer, University of British Columbia Vancouver, BC Canada) into the CMV promoter-driven pcDNA3.1 (Invitrogen/Life Technologies GmbH, Darmstadt, Germany) to obtain the hp300-pcDNA3.1 expression plasmid.…”
Section: Plasmid Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent studies have shown that artificial mutations of this CCACC element lead to decreased INS promoter activity (36,42). Although previous studies failed to identify protein complexes interacting with this region in beta-cell nuclear extracts (17,36), a recent study showed that in vitro translated GLIS3, a zinc-finger transcription factor that is mutated in patients with neonatal diabetes and congenital hypothyroidism (43), exhibits sequence-specific binding to this region (42). Multiple DNA binding factors may 367_-344del (-129_-106) c. bind to CCACC elements in vitro, and thus future studies are warranted to determine if additional factors act through this element in vivo in beta cells.…”
Section: Discussionmentioning
confidence: 99%
“…This sequence is conserved among a subset of mammalian species (Fig. 3A) and mutagenesis of multiple bases neighboring this dinucleotide impairs INS promoter activity (36). We constructed insulin promoter fragments carrying the point mutations c.-331(C > G, C > A) and c.-332C > G. The point mutations induced up to 90% reduction in transcriptional activity, while a control mutation, c.-339G > A, did not alter the transcriptional activity in pancreatic beta-cell lines (Fig.…”
Section: Recessive Ins Mutations Uncover Essential Regulatory Sequencmentioning
confidence: 99%